2020
DOI: 10.1155/2020/4868797
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic Efficacy of Strongyle Nematodes to Ivermectin and Fenbendazole on Working Donkeys (Equus asinus) in and around Hosaena Town, Southern Ethiopia

Abstract: Background. Gastrointestinal helminth parasite infection is a major influencing factor against profitability of working equines all over the world. Objectives. A study was conducted from October 2016 to May 2017 in and around Hosaena to determine the efficacy of benzimidazole (BZ) and avermectin (AVM) chemical groups against strongyle nematodes in working donkeys. Methods. A total of 230 donkeys from Hosaena, Soro, Anlemo, and Gombora were randomly allocated into 5 groups of 46 donkeys in each group. All group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
11
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 28 publications
7
11
1
Order By: Relevance
“…In the current study, 70.2% of the equines were infected with a severe degree of strongyle infection, while 25.9% of the equines harbored a moderate level of strongyle infection and a mild degree of infection was recorded in 3.85% of equines of the study sites. This observation was comparable with the previous report by Fesseha et al 39 in Hosaena who reported an EPG of 73%, 23.9%, and 3.04% of a severe, moderate, and a mild degree of strongyle infection in donkeys, respectively. Hutchison and Mfitlidoze 40 in Australia, also reported 80% of horses were infected with gastrointestinal parasites.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, 70.2% of the equines were infected with a severe degree of strongyle infection, while 25.9% of the equines harbored a moderate level of strongyle infection and a mild degree of infection was recorded in 3.85% of equines of the study sites. This observation was comparable with the previous report by Fesseha et al 39 in Hosaena who reported an EPG of 73%, 23.9%, and 3.04% of a severe, moderate, and a mild degree of strongyle infection in donkeys, respectively. Hutchison and Mfitlidoze 40 in Australia, also reported 80% of horses were infected with gastrointestinal parasites.…”
Section: Discussionsupporting
confidence: 92%
“…The decreased prevalence of migratory strongylids in the horses may be related to the fact that all of the study horses were cart horses, which are less exposed and, in some circumstances, limited from pasture. The prevalence of migratory strongylids in donkeys wase lower than the previous findings of [ 1 – 3 , 7 , 10 , 31 – 34 , 36 , 38 , 42 , 44 , 50 , 52 57 ], who indicated a prevalence of 5.82, 44.55%, 59.1%, 60.6%, 66.07, 70.8%, 76%, 79.7%, 80.2%, 81%, 82.75%, 87.81%, 87.8%, 88.21%, 95.5, 99%, 100%, 100%, 98.2%, 100%, and 100%, respectively. Strongyle infections are more common, which is consistent with their biology and epidemiology, as these parasites take longer to complete their life cycle and their burden has fluctuated over time due to anthelminthic stresses [ 14 ].…”
Section: Discussioncontrasting
confidence: 68%
“…Gastrointestinal parasite infection directly affects the health and production of working equines, which contributes to the reduction in their work output and, ultimately, in the income of the owner and the community [ 31 , 32 ]. In this study, the overall prevalence of gastrointestinal helminth was 78.5%, where a higher prevalence of GI parasitism was recorded in donkeys (91%) than horses (63%).…”
Section: Discussionmentioning
confidence: 99%